Construção e aplicação de um Turbidímetro / Nefelômetro Microcontrolado Portátil - Santos, Vagner Bezerra dos (2009)
Development of a portable, simple and inexpensive equipment with adequate sensitivity for turbidimetric and/or nephelometric sequential analyses practically simultaneous is the aim of this study. In fact, in-situ and on-line analysis of chemical substances of interest (analytes) can be accomplished. This is requested mainly in situations in which the place is difficult to access or even in circumstances in which the physical- chemical characteristics of the samples should be unchanged. Thus, the equipment was applied in- situ sulfate determination in lake samples. Analytes of interest such as N-acetylcysteine, captopril and thiamine in pharmaceutical samples and potassium in isotonic beverages were also analyzed with the developed instrumentation. The PMTN (Portable Microcontrolled Turbidimeter Nephelometer) is made of LEDs (Light Emitting Diodes) as radiation sources, phototransistors as optical sensors and a PIC microcontroller (Peripherical Interface Controller) as processing unit for control and data acquisition. The PMTN was tested and calibrated properly according to the norms establish by ISO 7027 for equipment base on LEDs as radiation source. The PMTN was applied to determine the concentration of analytes and compared with the reference or validated methods for each analyte, as described in the literature. In general, results agreed at the 95% confidence level were obtained. The detection limits and quantification for the determination of the several analytes were agreed with in some better cases than those found in the literature. On average, the PMTN furnished two decades of linear range of concentration and a reproducibility (RSD) lower than 3.0 % with an average error of less than 5.0 % were also obtained.